Soluble Cell Wall Polysaccharides Released from Pea Stems by Centrifugation : II. EFFECT OF ETHYLENE - Terry, Maurice E. (1981)
The effect of ethylene on cell wall metabolism in sections excised from etiolated pea stems was studied. Ethylene causes an inhibition of elongation and a pronounced radial expansion of pea internodes as shown by an increase in the fresh weight of excised, 1-cm sections. Cell wall metabolism was studied using centrifugation to remove the cell wall solution from sections. The principal neutral sugars in the cell wall solution extracted with H(2)O are arabinose, xylose, galactose, and glucose. Both xylose and glucose decline relative to controls in air within 1 hour of exposure to ethylene. Arabinose and galactose levels are not altered by ethylene until 8 hours of treatment, whereupon they decline in controls in air relative to ethylene treatment. When alcohol-insoluble polymers are fractionated into neutral and acidic polysaccharides, xylose and glucose predominate in the neutral fraction and arabinose and galactose in the acidic fraction. Ethylene depresses the levels of xylose and glucose in the neutral fraction and elevates arabinose and galactose in the acidic fraction. Ethylene treatment does not affect the level of uronic acids extracted with H(2)O; however, the level of hydroxyproline-rich proteins in this water-extracted cell wall solution is increased by ethylene. Extraction of sections with CaCl(2) results in an increase in the levels of neutral sugars particularly arabinose. Ethylene depresses the yield of arabinose in calcium-extracted solution relative to controls in air. Similarly, extraction with CaCl(2) increases the yield of extracted hydroxyproline in ethanol-insoluble polymers and ethylene depresses its level relative to controls. Metabolism of uronic acids and neutral sugars and growth in response to ethylene treatment contrast markedly with auxin-induced polysaccharide metabolism and growth. With auxin, sections increase mostly in length not radius, and this growth form is associated with an increase in the levels of xylose, glucose, and uronic acids. With ethylene, on the other hand, stem elongation is suppressed and expansion is promoted, and this growth pattern is associated with a decrease in xylose and glucose in the ethanol-insoluble polysaccharides.